Arc erosion behavior and mechanism of Cu/Cr20 electrical contact material. (September 2017) - Zhu, Shunxin; Liu, Yong; Tian, Baohong; Zhang, Yi; Song, Kexing
Abstract: Cu/Cr20 material was prepared by spark plasma sintering. And then the arc-erosion tests of electrical contacts were carried out under the condition of constant current load with JF04C contact material test system. The trend of mass change (loss and transfer) of the Cu/Cr20 contact material was analyzed, when the current is less than 35 A, mass loss of material increases with the increase of current, when the current is 40 A, material is transferred from cathode to anode. The SEM was employed to investigate the surface morphologies of arc-eroded specimens of the Cu/Cr20 electrical contact materials. In accordance with the relevant experimental data, the relationship among arcing time, arc energy, and welding force was analyzed, and there is a linear relationship between the arcing time ( t ) and arc energy( E ) ( E = 143.9 t − 158.3 ). The results indicate that the phenomena of material melting and transfer are caused by DC arc. There are molten pools, pits, porosity, cracks and coral structure distributed on the surface of contacts. And composition segregation phenomenon occurred on the arc erosion layer at the same time. With the increasing of operation times, there is a positive linear correlation between arc energy and the arcing time. Highlights: In this study, Cu/Cr20 composites material was prepared by Spark Plasma Sintering in a vacuum environment. The arc erosion morphology includes pits, cracks, et al. and component segregation occurred in the ablated layer. The formation mechanism of molten pool and cross section element distribution after arc erosion were explained. There is a linear relationship between the arcing time and the arc energy. E = 143.9 t − 158.3 .